2002
DOI: 10.1038/sj.cgt.7700447
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced adenovirus gene transfer, an efficient and specific gene delivery technology for cancer gene therapy

Abstract: A main issue for further clinical progress of cancer gene therapy is to develop technologies for efficient and specific delivery of therapeutic genes to tumor cells. In this work, we describe a photochemical treatment that substantially improves gene delivery by adenovirus, one of the most efficient gene delivery vectors known. Transduction of two different cell lines was studied by microscopy, flow cytometry, and an enzymatic assay, employing a -galactosidase -encoding adenovirus. The photochemical treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 24 publications
2
57
0
Order By: Relevance
“…24,25 However, in spite of significant increase, they were not able to transfect the entire population of cells compared to the results obtained for photochemically enhanced adenovirus-mediated gene delivery. 26 By relying on the idea that the effectiveness of nonviral transfection systems depends on the cell cycle status, 27 they investigated the role of the cell cycle status in photochemical transfection mediated by two types of synthetic transfection agents: a cationic polypeptide polylysine (polyfection) and a cationic lipid formulation N-(2-amino ethyl)-N,N-dimethyl-2,3-bis(tetradecyloxy)-1-propanaminium bromide/dioleoylphosphatidyl ethanol amine. 28 The effect of photochemical treatment on EGFP expression in cells illuminated in different cell cycle phases was compared.…”
Section: Intelligent Polymeric Vectors In Gene Therapymentioning
confidence: 99%
“…24,25 However, in spite of significant increase, they were not able to transfect the entire population of cells compared to the results obtained for photochemically enhanced adenovirus-mediated gene delivery. 26 By relying on the idea that the effectiveness of nonviral transfection systems depends on the cell cycle status, 27 they investigated the role of the cell cycle status in photochemical transfection mediated by two types of synthetic transfection agents: a cationic polypeptide polylysine (polyfection) and a cationic lipid formulation N-(2-amino ethyl)-N,N-dimethyl-2,3-bis(tetradecyloxy)-1-propanaminium bromide/dioleoylphosphatidyl ethanol amine. 28 The effect of photochemical treatment on EGFP expression in cells illuminated in different cell cycle phases was compared.…”
Section: Intelligent Polymeric Vectors In Gene Therapymentioning
confidence: 99%
“…20 PCI is based on disruption of the endocytic compartments in cells by light specific activation of photosensitizing compounds such as sulfonated aluminium phthalocyanines or sulfonated tetraphenyl phorphines that localize in the endocytic vesicles. 21 The mechanism and benefit of the technology has earlier been documented for nonviral vectors.…”
Section: Introductionmentioning
confidence: 99%
“…The light dose corresponding to B50% cytotoxicity was used, as PCI has been shown to be most efficient when 50% of the cells are killed. 5 The expression levels of b-galactosidase or GFP were assayed 48 hours post-infection by flow cytometry.…”
Section: Photochemical Treatmentmentioning
confidence: 99%
“…[1][2][3][4] PCI was initially documented to increase the delivery of proteins and nonviral vectors, but the technology has also shown to enhance adenoviral gene transfer by up to 20-fold. 5 Adenovirus is one of the most commonly used vectors for cancer gene therapy. However, clinical studies have revealed that limiting factors are immune response in humans and the large number of viral particles needed to obtain therapeutic effect.…”
mentioning
confidence: 99%